(untitled) - Freidin, Jesse (Guilford, Connecticut, 2017)
Without volunteers, our nation’s animal shelter system simply would not exist. Volunteers speak for those that cannot speak, pick up the pieces for abandoned animals that have been let down by previous owners or unfortunate circumstances, and do whatever it takes to heal the deepest of wounds.In Finding Shelter, award-winning photographer Jesse Freidin shows the softer side of this story. He witnessed firsthand how many of the volunteers were able to mend their own emotional hurts with the love the shelter animals gave back to them, and how the power of these relationships transforms shelters into places where humans and animals can heal together. This realization propelled him to take a two-year journey across the country to document the tenderness and healing, beauty and joy he encountered within the shelter system. The result is a heartwarming inspiration for people to look differently at how to save shelter pets. In Finding Shelter, Freidin sparks a new discussion about animal rescue and what it feels like to truly love an animal.
Keywords: Nơi trú ấn của động vật,Animal shelters; Hoa Kỳ,United States